2015
DOI: 10.1007/s00603-015-0798-7
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Model for Predicting Rockfall Trajectory Direction

Abstract: A methodology for the experimental investigation of rockfall in three-dimensional space is presented in this paper, aiming to assist on-going research of the complexity of a block's response to impact during a rockfall. An extended laboratory investigation was conducted, consisting of 590 tests with cubical and spherical blocks made of an artificial material. The effects of shape, slope angle and the deviation of the post-impact trajectory are examined as a function of the pre-impact trajectory direction. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…As direction difference increases, the deviation becomes positive, which means that the change in direction follows the direction of slope's aspect. These findings are consistent with trends described by Asteriou and Tsiambaos (2016), but the deviation of the actual trajectory is significantly lower. This can be attributed to the different conditions (i.e., block shape, slope material, slope roughness, incident velocity and angle, and scale) between the experimental program conducted by Asteriou and Tsiambaos (2016) and the Ponti rockfall event.…”
Section: Lateral Dispersion and Deviationsupporting
confidence: 82%
See 2 more Smart Citations
“…As direction difference increases, the deviation becomes positive, which means that the change in direction follows the direction of slope's aspect. These findings are consistent with trends described by Asteriou and Tsiambaos (2016), but the deviation of the actual trajectory is significantly lower. This can be attributed to the different conditions (i.e., block shape, slope material, slope roughness, incident velocity and angle, and scale) between the experimental program conducted by Asteriou and Tsiambaos (2016) and the Ponti rockfall event.…”
Section: Lateral Dispersion and Deviationsupporting
confidence: 82%
“…Thus, impact velocity should be greater, which is possible if the launch velocity of the previous impact was higher than the assumed minimum. For the cases where V cor < 1, it is observed that kinematic COR ranges between 0.55 and 1.0 and presents smaller variation compared to the normal or tangential coefficient of restitution, similar to what was previously reported in the relevant literature (i.e., Asteriou et al, 2012;Asteriou and Tsiambaos, 2016).…”
Section: Coefficients Of Restitutionsupporting
confidence: 74%
See 1 more Smart Citation
“…A large number of tests have shown that spherical falling blocks have higher and more consistent COR values than cubic blocks (Asteriou and Tsiambaos, 2016), and so that the same control methods will have greater difficulty in containing their effects than those of non-spherical blocks with the same properties. This indicates that spherical rocks are a common hazard and that if a cushion is designed to resist these, it can also effectively resist non-spherical rocks.…”
Section: Experimental Materials and Apparatusmentioning
confidence: 99%
“…A comparative analysis of road accidents in the Aosta Valley was then undertaken to verify the methodology. Asteriou and Tsiambaos (2016) examined the effects of rock shape by performing tests with spherical and cubic blocks, finding that spherical blocks show higher and more consistent coefficient of restitution (COR) values than cubic blocks. Prina Howald et al (2017) evaluated the protective capacity of existing and newly proposed protection measures and considered the possible reclassification of hazard as a function of the mitigation role played by the measure.…”
Section: Introductionmentioning
confidence: 99%